Anaplastic lymphoma kinase-positive large cell lymphoma of the anterior skull base: Report of an unusual case and review of the literature - Jamshidi, Pouya (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Anaplastic lymphoma kinase (ALK)-positive anaplastic large cell lymphoma (ALCL) is a rare peripheral T-cell lymphoma, accounting for approximately 3% of adult non-Hodgkin lymphomas (NHL). In this report we describe an unusual case of an ALK(+) ALCL, which presented as an aggressive mass involving upper nasal cavity and anterior skull base. The pathogenesis, histopathology with radiologic correlations, and management of this case are reviewed. CASE DESCRIPTION: A 28-year-old Asian female presented with a 3-month history of nasal congestion culminating in epistaxis. Physical examination was notable for a tissue mass obstructing nasal cavity and the sphenoid sinus. Computed tomography (CT) and magnetic resonance (MR) imaging revealed a lesion primarily involving the upper nasal cavity extending intracranially through the cribriform plates into the anterior cranial fossa. Histologic and immunohistochemical analysis of the specimen obtained through a transnasal biopsy revealed an ALK(+) ALCL. The patient underwent two cycles of chemotherapy and focal radiation therapy, achieving minimal residual disease. The patient remained neurologically unchanged with stable minimal residual disease at the 1-year follow-up. CONCLUSIONS: To the best of our knowledge, this is the first case of an ALK(+) ALCL that presented as an aggressive upper nasal cavity and anterior skull base lesion. This case report highlights the importance of multi-modality approaches including preoperative imaging and tissue biopsy for definitive diagnosis.